Dynamic simulation of a trigeneration system using an absorption cooling system and building integrated photovoltaic thermal solar collectors. (November 2021) - Jalalizadeh, Mohammad; Fayaz, Rima; Delfani, Shahram; Mosleh, Hassan Jafari; Karami, Maryam
Abstract: Solar systems are the most promising technologies to reduce building energy consumption. In recent years, one of the popular solar technologies is building integrated photovoltaic-thermal collectors, because of profitability and no need for separate architectural space. In this study, a new combination of glazed building integrated photovoltaic thermal solar collectors and an absorption cooling system, as a trigeneration system, to provide thermal and electrical energy demands of a case study residential building, is proposed. Dynamic simulation of the proposed system is performed using the TRNSYS-MATLAB co-simulator. Because there is no model for the glazed photovoltaic thermal solar collectors in TRNSYS, the thermal model of the glazed building integrated photovoltaic thermal solar collectors is developed in MATLAB and connected to the TRNSYS model. Taking into account the passive and active effects of the BIPVT system, as well as the allocation of thermal energy generation by the BIPVT system so that the absorption chiller is a priority, the cooling energy demand of the building is reduced by 36%. The result showed that the proposed system provides 29% (55.81 Mwh/year) of the annual building energy demand, i.e. 34% of the electrical energy demand and 22% of the thermal energy demands of the building. The annual solar fraction and the total efficiency of the trigeneration system are 28% and 18%, respectively. The findings indicate that the building energy consumption decreases significantly using the proposed system, which resulted in considerable energy and economic savings. Highlights: A trigeneration system using the glazed BIPVT and an absorption cooling system is proposed. The dynamic simulation of the proposed system is performed using the TRNSYS-MATLAB co-simulator. The cooling energy demand of the building is reduced by 36%. The proposed system provides 29% of the annual building electrical and thermal energy demand.